Energy metabolism and obesity : research and clinical applications - Donohoue, Patricia A. (Springer, 2017)
Energy Metabolism and Obesity: Research and Clinical Applications is a compilation of highly informative reviews written by undisputed leaders in the field. These authors elucidate the most important aspects of genetic background, neuropeptide secretion and action, neuronal pathways, adipokines, gut hormones, and environmental influences (physical activity, pharmacologic agents, and surgical alteration of the gastrointestinal tract), as well as the complex interactions among them. Understanding the physiology of energy storage and partitioning has become quite a daunting task. This title enables researchers and clinicians to face the challenge of understanding this complex topic and applying the information to the practice of obesity prevention and treatment. The excellent overviews in this book will undoubtedly provide readers with a better understanding of the multifaceted entity of obesity.